COLLABORATION OF THREE STAKEHOLDERS ‘TRISULA’ IN REALIZING THE COMPLETE VILLAGE MAP - Westi Utami Utami; Fajar Buyung Permadi; Taufik Nur Rokhman (Jurnal Sosioteknologi, 2021)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) is targeting the realization of thevalid complete village map. This strategic program is carried out by mapping all land parcels including physical and juridical data so that an accurate land database can be created. This study aimed to analyze collaborations of three stakeholders: Land Office, City/Regency Government, and Village Government in realizing the complete village map. This study was conducted using a qualitative-descriptive method. Data collection was conducted in three ways: interview, secondary data, and observation field. Data analysis was carried out spatially on the main data and supporting data for the complete village map. The results of the study show that collaboration and data sharing (land registration maps, land value zone map, PBB block map, Regional Spatial Planning (Rencana Tata Ruang Wilayah - RTRW) map, and detailed Village Letter C map) between the three stakeholders are important variables for building the complete village. This study proves that the collaboration of the three stakeholders is able to accelerate the realization of a complete village database with results that match the requirements and criteria set by the Ministry of ATR/BPN. In addition, the data integration that was carried out can be used to create a one data village, which is expected to be able to provide input for the government in formulating policies.